a design research study of customised management development. - Shepherd, Wendy (Cranfield University, 2017)
This Design Research study of customised management development (CMD) develops an explanatory model of how CMD generates organisational level impact. The model makes a contribution to the management development literature by providing a plausible explanation of the connectivity between CMD as an input and performance as an organisational level outcome. The model is consistent with a realist perspective and suggests that CMD does not cause change, but changes the course of change that is already in process within the organisation through, inter alia social interactions and practice based learning. In contrast to prevailing more linear perspectives of the CMD process, the notion of the participant leaving their organisational context to be developed has been replaced with a representation of CMD where the organisation’s context is ever present within the development process. The practical validity of the model and its artefacts has been field tested at Cranfield School of Management. This has resulted in the implementation of a ‘Design for Impact’ process. The process utilises knowledge artefacts in the form of diagrams and design propositions that recommend what to do and what to avoid when designing interventions within specific organisational contexts. The model and knowledge artefacts that form the output of this research have been developed using a Design Research method. The method combines knowledge drawn from a systematic review of the literature with practitioner interviews. The application of the approach to the management development literature progresses the discussion from ‘How do we prove the organisational level impact of management development?’ to ‘How can we improve the organisational level impact of management development?’.
Keywords: Customised management development; input; performance; change; development process; design research method